Assessment of the adaptive potential and ecological plasticity of a new variety of spring barley Fermerskiy for Northwest Russia - Radyukevich Tatiana (EDP Sciences, 2021)
In Northwest Russia, creation and introduction of new varieties of cereals characterized by early maturity, high adaptive potential and ecological plasticity is one of the most important tasks. A new generation of barley varieties is needed that combines high yields with early maturity, high feed qualities of grain, and resistance to lodging and grain shedding. We carried out field and laboratory studies of a new variety of spring barley Fermerskiy in an experimental field of the Leningrad Research Institute of Agriculture "Belogorka". In 2021, Fermersky was transferred for state variety testing. The variety is midseason and the growing season is 72–87 days. Over three years of competitive variety testing (2018–2020), the yield increase was 1.25 t/ha relative to the Suzdalets standard (3.12 t/ha). The highest yield of 5.27 t/ha was obtained in 2019, under conditions of low moisture supply. The average index of ecological plasticity (Jsp) was 1.48 (min 1.11, max 1.94). The adaptive potential (ds/dk) was 7.91 (min 6.92, max 9.08), The Fermerskiy variety consistently formed a high yield and was characterized by ecological plasticity, early maturity, and resistance to diseases and lodging.